Redefining the Role of Sons in Mangulewa-Ngada Matrilineal Inheritance: A Sociolegal Reinterpretation of Tradition and Change - Yosefina Daku; Afriansyah Tanjung; Kornelius Joseph Paga Meka; Arum Anggraeni Maulida (Universitas Negeri Semarang, 2025)
This study investigates the evolving social and functional roles of sons within inheritance practices under the Mangulewa matrilineal system in Ngada Regency, East Nusa Tenggara. In this system, lineage and property rights are traditionally transmitted through the maternal line, positioning women as formal heirs to ancestral houses and family assets. Despite their exclusion from formal inheritance, sons retain significant cultural roles embedded in customary obligations and symbolic authority. This research aims to analyze how the roles of sons are conceptualized, negotiated, and reconstructed within the dynamics of contemporary Mangulewa society. The study employs a qualitative socio-legal approach grounded in a social constructivist paradigm, incorporating perspectives of legal pluralism and living law. Data were collected through in-depth interviews with traditional leaders, family heads, and community members, complemented by document analysis and direct observation of customary practices. The findings demonstrate that sons occupy strategic roles as protectors, mediators, and custodians of family dignity and ritual continuity, particularly in relation to the Ngadhu–Bhaga houses as central symbols of lineage identity. Their participation in marriage negotiations, ceremonial duties, and conflict resolution reflects a form of socially acknowledged yet informally constituted authority. At the same time, processes of modernization, migration, and increasing interaction with state legal systems have contributed to shifting interpretations of gender roles and inheritance claims. This study contributes to socio-legal scholarship by offering an empirically grounded account of how non-heir actors sustain and reshape matrilineal inheritance systems. It advances the discourse on legal pluralism by demonstrating that inheritance practices are not solely determined by formal entitlement but are continuously reconstructed through cultural negotiation, thereby highlighting the adaptive capacity of customary law in responding to social change.